Nutrition in the life cycle laboratory manual - Querubin, Milagros P.; Panlasigui, Leonora N. (Manila Meriam & Webster Bookstore, 1994)
Purpose: "...designed to give an overview of nutrition principles in the management of diets for the at-risk groups of the population such as pregnant and lactating women; infants; pre-school and school-age children, teenagers, athletes and the elderly."
Content/s: Diet. Nutrition (infant, school-age child, adolescence, aging, athlete). Pregnancy and lactation. RDA for Filipinos. Weight. Height. Breast milk. Sterilization. Marasmus and Kwashiorkor. Weight-for-age survey.
"This laboratory manual in nutrition in the life cycle is designed to give an overview of nutrition principles in the management of diets for the at-risk groups of the population such as pregnant and lactating women; infants; preschool and school-age children; teenagers; athletes; and the elderly. It contains exercises on planning, preparation and evaluation of diets for the above mentioned population groups. Before each laboratory exercise, there is a brief discussion on the physiological and other characteristics, public health problems and nutrition education principles related to each stage of the life cycle. Local articles and researches are incorporated in these discussions. Relevant questions are at the end of each exercise can add to the learning experiences of the students. The exercises in this manual are the result of years of teaching experiences of the authors and other experts in the field. This manual is designed for a nutrition course at the college level and may be used as a reference in teaching nutrition to home economists, nursing and medical students, teachers, public health workers and other allied professionals."
Keywords: Nutrition -- Handbooks, manuals, etc; Nutrition -- Requirements